Broadband cavity-enhanced detection of magnetic field effects in chemical models of a cryptochrome magnetoreceptor. - Neil, SR; Li, J; Sheppard, D; Storey, J; Maeda, K; Henbest, K; Hore, P; Timmel, C; Mackenzie, S (American Chemical Society, 2014)
Broadband cavity-enhanced absorption spectroscopy (BBCEAS) is shown to be a sensitive method for the detection of magnetic field effects (MFEs) in two flavin-based chemical reactions which are simple models for cryptochrome magnetoreceptors. The advantages of optical cavity-based detection and (pseudo-white-light) supercontinuum radiation have been combined to provide full spectral coverage across the whole of the visible spectrum (425 < λ < 700 nm). This region covers the absorbance spectra of flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD) as well as their photogenerated radicals. To illustrate the power of this technique, BBCEAS has been used to record the spectral dependence of MFEs for photoinduced radical pairs formed in the intermolecular reaction of FMN with lysozyme and the intramolecular photochemistry of FAD. These reactions have been chosen for their photochemical similarities to cryptochrome proteins which have been proposed as key to the magnetic compass sense of many animals including birds. In experiments performed using low protein concentrations (10 μM) and 1 mm optical path-lengths, absorbance changes as small as 1 × 10(-7) (representing <0.1% MFEs) have been detected with good signal-to-noise offering the prospect of sensitive MFE detection in cryptochrome.